Banking reserves and currency reform - Bastable, C. F. (Statistical and Social Inquiry Society of Ireland, 1891)
The best test of the merits of a monetary or credit system is the fact that its operations attract no notice. As long as all goes well, people in general are quite content with efficient practical working, and, very wisely, do not trouble themselves with theoretical anomalies or defects. Unfortunately what is at one time a matter of purely speculative interest may at another affect the conditions of national prosperity, and become of grave practical moment.
Read Tuesday, 2nd June, 1891
Keywords: Bank reforms; Bank notes; 314.15